CAPACIDADE COMBINATÓRIA DE PROGÊNIES S3 DE MILHO EM TOPCROSSES COM DIFERENTES TESTADORES PARA FORRAGEM E GRÃOS - Silva, Carlos Augusto da (2017)
Maize is the most suitable species for forage production for silage purposes and the obtain new lines and hybrids with forage objective from populations obtained from commercial hybrids are viable strategy. This study aims to select S3 progeny maize, for the combining ability of forage, grains and bromatological quality characters and promising testers to the discrimination of the progenies through the genetic and phenotypic parameters of the topcrosses and estimates of the combining ability of testers. The 45 S3 progenies were obtained, which were cross-checked with the testers AG8025, 70.H26.1 e MLP102. Thus forming 3 essays conducted in randomized blocks with two replicates. Evaluated in the 2014/2015 harvest in the environments of Guarapuava and Rio Bonito do Iguaçu, in Paraná State. It was evaluated spike height, plant height, male flowering, grain yield, stay green, forage cycle, neutral detergent insoluble fiber, acid detergent insoluble fiber, dry matter yield and forage digestibility. Was performed individual and joint analysis of variance and individual and joint partial diallelic analysis, we estimated the components of the variance and genetic parameters for each topcross in each environment. The progenies 1.1, 15.3, 22.1, 31.3, 47.1, 57.2, 57.4, 71.1, 74.4, 79.2, 88.1, 88.4 and 90.2 and hybrids TC2-1.1, TC2-52.3, TC3-9.1, TC3-26.1, TC3-59.1, TC3-61.2 e TC3-90.2 in Guarpauava and hybrids TC2-8.2, TC3-21.1, TC3-47.1, TC3-49.1, TC3-74.4 e TC3-88.4 in Rio Bonito do Iguaçu were stood out for the characters related to grain yield. As the characters related to forage production, the progenies 1.1, 22.1, 29.1, 31.3, 65.5, 79.1, e 88.1 in Guarapuava, the progenies 4.1, 15.3, 24.1, 39.1, 47.1, 51.1, 57.2 e 90.2 in Rio Bonito do Iguaçu and the progenies 3.1, 17.2, 19.1, 45.1, 48.1, 62.2 e 88.4 in both environments were stood out. The AG8025 and 70.H26.1 testers provided greater exploration of the existing variability for forage characters. While the MLP102 tester was the most adequate to classify the progenies as AE and AP in both environments and for FM and PG in Rio Bonito do Iguaçu and the tester AG8025 stood out in the selection of progenies for FM and PG in Guarapuava.